THE EFFECTIVENESS OF DIFFERENTIATED LEARNING BASED ON LEARNING STYLES IN INCREASING INTEREST IN LEARNING SCIENCE: AN EMPIRICAL REVIEW 2021–2025 - Suci Okta Mela Dwisa; Farid Ahmadi; Bambang Subali; Ellianawati (RADJA PUBLIKA, 2026)
This study aims to review the effectiveness of differentiated learning based on learning styles in increasing interest in learning science through a systematic literature review. The research method used the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) approach, in which 1,264 initial articles were identified through various international and national databases, then screened through stages of eliminating duplication, screening based on title and abstract relevance, and feasibility testing based on full content. From this selection, 76 articles met the inclusion criteria and were analyzed in depth. The results of the study indicate that differentiated learning can significantly increase student interest in learning by increasing intrinsic motivation, active involvement in the learning process, and creating an inclusive and responsive learning environment to individual needs. In addition, differentiated learning is in line with the principles of the Independent Curriculum which focuses on personalized and flexible learning, thus providing opportunities for students to learn according to their styles and needs. Therefore, it is recommended that elementary school teachers implement differentiated learning strategies in a planned and sustainable manner by considering the variety of students' learning styles. This step is expected to optimize interest, motivation, and the quality of science learning, so that learning becomes more meaningful, enjoyable, and relevant for each student.